2015
DOI: 10.1590/1807-1929/agriambi.v19n10p967-972
|View full text |Cite
|
Sign up to set email alerts
|

Fruit quality of ‘Eva’ e ‘Princesa’ apples grown under nitrogen fertigation in semiarid climate

Abstract: The production of high quality fruits is a necessary factor for the adaptation and production of plant species with economic viability. Thus, an experiment was conducted from July 2012 to January 2013 to evaluate the fruit quality of the ‘Eva’ and ‘Princesa’ apple cultivars as a function of nitrogen fertilization in Petrolina, PE, Brazil. The experimental design consisted of randomized blocks, with treatments distributed in a factorial arrangement 2 x 4, corresponding to apple cultivars (Eva and Princesa) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 15 publications
(25 reference statements)
0
5
1
Order By: Relevance
“…Also, Ernani et al (2002) described a linear effect of K fertilization on N leaf concentration. Miranda et al (2015a) and Nava (2010) observed no N effect on apple fruit production. However, it is known that such an effect may vary with N fertilization method.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Also, Ernani et al (2002) described a linear effect of K fertilization on N leaf concentration. Miranda et al (2015a) and Nava (2010) observed no N effect on apple fruit production. However, it is known that such an effect may vary with N fertilization method.…”
Section: Resultsmentioning
confidence: 93%
“…The experimental design used was randomized blocks with treatments disposed in a factorial arrangement (4 x 4) referring to nitrogen doses (30, 60, 90, and 120 g of N plant -1 ) and potassium doses (30, 60, 90, and 120 g of K2O plant -1 ), with three replications and three plants in each parcel. N and K doses followed the previous studies of Ernani, Dias, and Flore (2002) and Miranda et al (2015a).…”
Section: Treatments and Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Ferreira (2014), as it has production capacity of up to six crops per year, West Indian cherry is demanding in terms of nutrients, mainly nitrogen (N) and potassium (K), both in the initial growth and development stage and in the production stage. Nitrogen fertilization is very important, as this nutrient influences plant growth, and its deficiency will directly affect fruit development and production (MIRANDA et al, 2015). Excess N, on the other hand, is also harmful because it stimulates excessive vegetative development of the plant, with effects on fruit quality and especially on the incidence of physiological disorders (ERNANI et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…However, fruit farming is expanding to non-traditional areas for temperate climate fruit crops (Lopes et al, 2013a;Miranda et al 2015a and2015b).…”
Section: Introductionmentioning
confidence: 99%